Sikap Pelanggan Millennial Indonesia Terhadap Iklan Online - Elvani Marcelin P.; Marry Marry; Marvin Anggasta; M. Fandhi Al-Baruu; Prisa Ngadianto (Universitas Prasetiya Mulya, 2018)
The number of Internet users in Indonesia are increasing rapidly, especially among Millennial Generation. Nowadays, almost all the transactions can be done through online. The main purpose is to understand Indonesia millennial customer attitude towards online advertising, Thus, give the marketers knowledge for effective strategy for publishing online advertising. Conceptual framework designed with five independent variable hypotheses: entertainment, informativeness, irritation, credibility, and incentives, which might affect millennial user attitudes towards online advertising. The result of this research which conducted among 209 respondents: Informativeness, entertainment and credibility have shown a direct positive and significant impact on consumer attitudes toward online advertising.